Applying ADDIE Methodology and Vision Inspection to Reduce Missing Parts Defects in Toy Manufacturing - Anastasia Lidya Maukar; Tiffany R Rianto (Universitas Katolik Parahyangan, 2026)
This research addresses missing parts defects in Advent Calendar toy production, a critical quality issue causing customer dissatisfaction and financial losses. The ADDIE methodology was applied as a systematic framework to analyze root causes, redesign ergonomic workstations with improved human-machine interactions, develop a vision inspection system, implement operator training, and evaluate outcomes. Results demonstrated significant improvements: defect reduction of 92% (from 53 to 4 cases), operator cycle time reduction of 75% (from 70.68 to 14.85 seconds), improved ergonomic conditions (RULA score decreased from 5 to 4), and labor cost savings of 75% (approximately IDR 1.2 billion annually). This study demonstrates that ADDIE provides a systematic, measurable approach for integrating human factors and technology to enhance inspection performance and support continuous improvement in manufacturing.